Aplastic Anemia Frequency and Management in Pediatric Liver Transplantations Due to Non-A-E Hepatitis - Ezgi Kıran Taşcı,; Miray Karakoyun,; Nihal Özdemir Karadaş,; Hamiyet Hekimci Özdemir,; Deniz Yılmaz Karapınar,; Can Karaca,; Funda Çetin,; Sema Aydoğdu, (Turkish Journal of Gastroenterology, 2021)
Background: Hepatitis-associated aplastic anemia (HAAA) is a rare complication that presented with bone marrow failure after acute hepatitis. HAAA usually occurs in adolescent men within 1-6 months following hepatitis. Most of HAAA’s etiology has non-A-E viral hepatitis. Methods: Our retrospective study included patients with acute fulminant hepatitis who had been treated in Ege University Pediatric Gastroenterology, Hepatology and Nutrition Department and İzmir Kent Hospital Clinical, laboratory, and epidemiological data of the patients were collected from the files. Results: In this study, 499 children underwent liver transplantation (LT) in two pediatric transplantation centers. Sixty-eight (13.6%) out of 499 patients, underwent liver transplantation due to fulminant hepatic failure (FHF). Therefore, a total of 64 patients (34 girls, 30 boys) with a diagnosis of FHF have included in the study. Thirty-two (50.0%) of 64 FHF were due to non-A-E hepatitis and 4 out of the 64 patients (6.2%) with FHF developed HAAA. All of the patients received prednisolone as immunosuppression treatment after LT. Three patients were also given Tacrolimus and 1 received an additional mycophenolate mofetil. One of the patients was given prednisolone and cyclosporine treatment without tacrolimus. Bone marrow transplantation was performed in 1 patient (25.0%). Two of the patients received immunosuppressive treatment including rabbit-derived anti-thymocyte globulin, cyclosporine, and initially prednisolone. Conclusion: In children who underwent liver transplantation for non-A-E FHF are at high risk to develop aplastic anemia. The clinicians should be alert after orthotropic liver transplantation patient could develop aplastic anemia and early treatment with immunosuppressive therapies result in a more successful outcome. Cite this article as: Kıran Taşcı E, Karakoyun M, Özdemir Karadaş N, et al. Aplastic anemia frequency and management in pediatric liver transplantations due to non-A-E hepatitis. Turk J Gastroenterol. 2021; 32(3): 313-317.